The Janus factor : trend follower's guide to market dialectics - Anderson, Gary Edwin, 1942- (Hoboken, New Jersey : Bloomberg Press, An Imprint of Wiley, 2012)
Tap into feedback loops to unravel market trends and discover profitable trading opportunities The Janus Factor presents an innovative theory that describes how feedback loops determine market behavior. The book clearly shows how the theory can be applied to make trading more profitable. The metaphor of the two-faced god Janus is used to reflect alternating market environments, one dominated by trend followers and the other by contrarian bargain hunters. In this book, author Gary Anderson puts forth a systematic view of how positive and negative feedback drive capital flows in the stock market.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Speculation; Investment analysis; Investments; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis; Investments; Speculation; Electronic books